History of tuberculosis is associated with lower exhaled nitric oxide levels in HIV-infected children. (1st September 2019) - Sovershaeva, Evgeniya; Kranzer, Katharina; Mchugh, Grace; Bandason, Tsitsi; Majonga, Edith D.; Usmani, Omar S.; Rowland-Jones, Sarah; Gutteberg, Tore; Flægstad, Trond; Ferrand, Rashida A.; Odland, Jon Ø.
Abstract : Objective: HIV disrupts host defense mechanisms and maintains chronic inflammation in the lung. Nitric oxide is a marker of lung inflammation and can be measured in the exhaled air. We investigated the relationship between exhaled nitric oxide (eNO), HIV status and airway abnormalities in perinatally HIV-infected children aged 6–19 years. Design: A cross-sectional study. Methods: HIV-infected individuals on antiretroviral therapy and HIV-uninfected children with no active tuberculosis (TB) or acute respiratory tract infection were recruited from a public hospital in Harare, Zimbabwe. Clinical history was collected and eNO testing and spirometry was performed. The association between eNO and explanatory variables (HIV, FEV1 z -score, CD4 + cell count, viral load, history of TB) was investigated using linear regression analysis adjusted for age, sex and time of eNO testing. Results: In total, 222 HIV-infected and 97 HIV-uninfected participants were included. Among HIV-infected participants, 57 (25.7%) had a history of past TB; 56 (25.2%) had airway obstruction, but no prior TB. HIV status was associated with lower eNO level [mean ratio 0.79 (95% confidence interval, 95% CI 0.65–0.97), P  = 0.03]. Within the HIV-infected group, history of past TB was associated with lower eNO levels after controlling for age, sex and time of eNO testing [0.79 (95% CI 0.67–0.94), P  = 0.007]. Conclusion: HIV infection and history of TB were associated with lower eNO levels. eNO levels may be a marker of HIV and TB-induced alteration in pulmonary physiology; further studies focused on potential causes for lower eNO levels in HIV and TB are warranted.